Revitalization of Fisheries Production Factors Supporting the Income of Traditional Fishermen in Tanjung Medang Village, Bengkalis - Pazli Pazli; Irwan Iskandar; Hendrini Renola Fitri; Rahmat Kurniawan; Herliana Rahmi; Nurhayati Nurhayati (Eduvest - Journal of Universal Studies, 2024)
Coastal fisheries in Tanjung Medang Village, North Rupat District, Bengkalis Regency play an important role in shaping the economic characteristics and culture of its community. Physically, the North Rupat District is predominantly divided into residential areas along the inter-village roads and coastal areas that serve as the primary source of livelihood for most of its population. Now, North Rupat District has become a destination for both residents and visitors, impacting the existence of increasingly complex local economic resources and wisdom along the coastal areas of North Rupat District. Revitalization of coastal fisheries production factors is needed to improve economic life. Therefore, what model of economic development policy is needed to access traditional local economic resources to reduce local poverty? What kind of revitalization is required for traditional fishermen to utilize maritime economic resources fairly for the local population? The economic development policy for alternative marine economic resources involves integrating and collaborating the rights and obligations of state actors, private actors, and the public in maritime politics and economics. The revitalization of coastal fisheries production factors includes organizing the ecological integration of areas as traditional fishing grounds, tourism economic areas, and the originality of traditional culture across various disciplines, as well as fostering cultural integration among stakeholders and intergenerational concern among the Tanjung Medang community.